Structural, morphological, optical, and electrical properties of TiO2/ZnO rods multilayer films as photoanode on dye-sensitized solar cells. Issue 1 (February 2021) - Himmah, S W; Diantoro, M; Astarini, N A; Tiana, S K G; Nasikhudin,; Hidayat, A; Taufiq, A
Abstract: TiO2 nanoparticles have been widely studied as photoanode materials in DSSC due to the high surface area. Still, TiO2 nanoparticles exhibit weak light scattering which limiting red light absorption. On the other hand, one-dimensional structures such as rods demonstrate an increase in the light scattering. ZnO has undergone many structural modifications and exhibits higher mobility than TiO2 . The combining characteristics of TiO2 nanoparticles and ZnO rods can improve photoanode performance. Therefore, the efficiency of DSSC can be increased. The TiO2 /ZnO rods photoanodes were fabricated in the following steps. First, TiO2 nanoparticles were deposited on the conductive surface of ITO-Glass to form a double layer using the spin-coating method. Meanwhile, we prepare ZnO rods grown on the TiO2 nanoparticles layer using the hydrothermal method by varying Zinc Nitrate Tetrahydrate precursors (20; 30; 50; and 100 mM). Several physical characterizations have been carried out, including XRD, SEM, FTIR, UV-VIS, and Keithley SourceMeter 2400 equipped with a solar simulator 100 mW/cm 2 . Based on the results, the increasing concentration of Zinc Nitrate Tetrahydrate precursor affects the structural, morphological, optical, and electrical properties of TiO2 /ZnO rods multilayer photoanode and reaches the optimum point at 50 mM.